(untitled) (Journal of Parents and Teachers, 2026)
Reading old maps, whilst complicated in some respects, provides not only geographical information but also reveals the cultural and religious concepts on which cartography was based. The Orbis Terrarum (1472) is considered the first printed map, published in Germany. It was not a deliberate publication of the map itself, but rather the publication of Saint Isidore of Seville’s magnum opus *Etymologies* (630 AD), within which the map was found. The Lübeck map (1475) was the first to be produced specifically for publication, appearing in the book *Rudimentum Novitiorum*, which was studied by future clergy. This article offers an analysis of both maps.